Correlation Between EFL Learners Self-Confidence and Speaking Skill - Hasan Hasan; Muhammad Hanafi; Andi Sadapotto (MAJESTY JOURNAL, 2020)
This article aims to describe whether there is a relationship between students 'self-confidence and students' speaking abilities. This study uses cluster sampling methods and oral tests. The population in this study were VII grade students of SMPN 9 Pinrang. The total population is 104 students. The sample used was class VIIL.1 totaling 28 students. The method used in speech evaluation is an oral test. The results of research using Pearson Product Moment obtained r count value of 0.700 and with the product value of r products when products with N = 28 found 0.478 at 1% significance level and found 0.374 at a significant level of 5%. To find out the level of product moment correlation the coefficient of 0.61-0.80 = substantial. This can be seen in the results of the analysis, namely: 0.700> 0.478 (5%) and 0.700 0.374 (1%) with db: 28. This means that Ho is rejected and Ha is accepted. The conclusion of this research is that there is a significant relationship between students 'self-confidence and the eight-year students' speaking ability in SMPN 9 Pinrang.